2011
DOI: 10.1093/cvr/cvr148
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-mediated Th17 differentiation through RORγt is essential for the initiation of experimental autoimmune myocarditis

Abstract: IL-6-mediated induction of Th17 cells is critical for the onset of EAM, but not for its progression. IL-6/Th17 signalling could be a promising therapeutic target for the prevention of myocardial inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 23 publications
4
60
0
Order By: Relevance
“…IL-17, a potent inflammatory cytokine, induces the expression of numerous proinflammatory cytokines, chemokines, and metalloproteinases, and plays a major role in neutrophil proliferation, survival, and chemotaxis [35,36]. Furthermore, some reports indicate that Th17 cells contribute to the pathogenesis of EAM [28,29,[37][38][39]. According to the above investigation, HMGB1 blockade attenuates cardiac pathological changes and reduces the number of infiltrating inflammatory cells (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…IL-17, a potent inflammatory cytokine, induces the expression of numerous proinflammatory cytokines, chemokines, and metalloproteinases, and plays a major role in neutrophil proliferation, survival, and chemotaxis [35,36]. Furthermore, some reports indicate that Th17 cells contribute to the pathogenesis of EAM [28,29,[37][38][39]. According to the above investigation, HMGB1 blockade attenuates cardiac pathological changes and reduces the number of infiltrating inflammatory cells (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The recently identified Th17 subset 142 has been implicated in the onset of chronic myocarditis. 143 These cells secrete high levels of IL-17 and have been implicated in autoantibody production. 142,144 Research conducted on the Th17 subset in the context of CVB3 myocarditis suggests that these cells may contribute to chronic myocarditis through persistent inflammatory signals provided by secretion of IL-17.…”
Section: T-helper 17 Cells Play a Role In Chronic Inflammationmentioning
confidence: 99%
“…Enhanced IL-17 and Th17 specific transcription factor, ROR␥t, were also increased consistent with expansion of this cell type. 143 Interleukin-17 and its various isotypes can induce expression of TNF-␣ and Th2 responses, which in turn induce a prolonged inflammatory environment that might foster the production of auto-antibodies. Though autoimmune mechanisms of damage to the heart during chronic myocarditis may seem to be exclusive of the initial infectious insult, there is reason to believe that virus infection and inflammation are more interdependent than previously thought.…”
Section: T-helper 17 Cells Play a Role In Chronic Inflammationmentioning
confidence: 99%
“…For Th17 cells, substantial evidence had demonstrated that they are involved in the pathogenesis of inflammatory diseases. It had been found that anti-IL-6 treatment could reduce the proportion of Th17 cells, reducing the inflammatory reaction of autoimmune myocarditis [19]. In viral myocarditis, Yang et al found that administration of recombinant IL-23 reduced the percentage of Th17 cells and inflammation in mice [20].…”
Section: Discussionmentioning
confidence: 99%